Annual World Bank Conference on Development Economics 1995 (Washington World Bank Publications, 1996)
Annotation The 1995 conference continued the tradition of holding a roundtable discussion related to the subject of the forthcoming annual World Development Report (*), in this case, economies in transition. The conference addressed four themes: redi stribution with growth; demographic change and development; aid and development; and fiscal decentralization. Among the articles included in the 1995 proceedings are: - Argentina's Miracle? From Hyperinflation to Sustained Growth. Domingo F. Cavallo and Guillermo Mondino - Inequality, Poverty, and Growth: Where Do We Stand? Albert Fishlow - Government Provision and Regulation of Economic Support in Old Age. Peter Diamond - Is Growth in Developing Countries Beneficial to Industrial Countries? Richard N. Cooper - Fiscal Federalism and Decentralization: A Review of Some Efficiency and Macroeconomic Aspects. Vito Tanzi.
Scholarly & Professional
Keywords: Financial literacy; Developing Countries -- Economic Conditions; World Bank